Pemberdayaan Muslimatan Jumat dalam Pelestarian Tradisi Keagamaan dan Penguatan Solidaritas Sosial di Desa Tunggak Cerme - Nurul Hidayah; Devy Habibi Muhammad; Audi Pramudita; Siti Aisyah; Khoridatul husnia (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service program aims to empower the Muslimatan Jumat group in Tunggak Cerme Village, Wonomerto District, Probolinggo Regency, in preserving religious traditions and strengthening social solidarity within the local community. The method applied was Participatory Action Research (PAR), actively involving around 200 members of Muslimatan in every stage of the program, from preparation and implementation to evaluation. The preparation stage was carried out through observation and coordination with community leaders to identify routine activities and formulate program objectives. During the implementation stage, the KKN team assisted routine activities such as istighotsah, tahlilan, and social gatherings, while also providing interactive counseling and facilitating group discussions on traditions and social solidarity. The evaluation was conducted through small-scale forums to collect feedback, suggestions, and reflections from members. The results indicate that the program successfully increased community awareness of the importance of preserving religious traditions, strengthened social bonds, and encouraged youth participation in safeguarding local culture. Thus, Muslimatan Jumat can be regarded as a driving force in maintaining the spiritual and social values of rural communities.